The Influence of Transformational Leadership on Organizational Commitment with Empowerment as Mediation in Bank Indonesia Aceh Province - Imilda; Ihsanuddin; Jamil, Muhammad (Indonesian Journal Economic Review (IJER), 2022)
The purpose of the study was to determine the significant influence between transformational leadership and include empowerment as an intervening variable that bridges organizational commitment as the dependent variable and transformational leadership as an independent variable. The object of this research is the employees of Bank Indonesia Aceh Province in Banda Aceh. The Probability Sampling method (easy sample) has been chosen to obtain the data required for this study. This study used 61 respondents. Data analysis uses Path Analysis or path analysis with the computer program SPSS (Statistical Product and Service Solution) version 16. In the first equation, the effect of transformational leadership on empowerment is 50%. In the second equation, the effect of transformational leadership on organizational commitment is 40.6%, while the influence of empowerment on organizational commitment is 48.1%. The last equation shows that empowerment mediates the relationship between transformational leadership and organizational commitment by 19.5%.